Fiber Temperature Sensor Utilizing a Thermomechanical MEMS Detector - Cirkinoglu, Huseyin Ozan; Bilgin, Habib; Civitci, Fehmi; Torun, Hamdi; Ferhanoglu, Onur (Journal of lightwave technology, 2016)
We propose a novel fiber sensor utilizing a thermomechanical MEMS element at the fiber tip. Owing to its Parylene/Titanium bimaterial structure, the MEMS membrane exhibits an out-of-plane displacement with changing temperature. Together with the MEMS element, the embedded diffraction grating forms an in-line interferometer, from which the displacement as well as the temperature can be deduced. The fabricated detector is placed at the single-mode fiber output that is collimated via a graded index lens. This novel architecture allows for integrating MEMS detectors on standard optical fibers, and easy substitution of the MEMS detector element to alter the measurement range and the response time of the sensor. Temperature and time-constant measurements are provided and verified with reference measurements, revealing a temperature sensitivity better than 20 mK and 2.5-ms response time, using low-cost laser source and photodetectors.